2024
DOI: 10.1111/jocn.17052
|View full text |Cite
|
Sign up to set email alerts
|

Insights on spirituality and bereavement: A systematic review of qualitative studies

Helga Martins,
Joana Romeiro,
Tiago Casaleiro
et al.

Abstract: AimTo describe a synthesis of the experience related to the spirituality of those living a bereavement journey in primary qualitative studies.DesignA systematic review of qualitative studies.Data SourceA systematic review was carried out in March 2019 and was updated in January 2023. Searching was accomplished by an online database, such as CINAHL, MEDLINE, PsycINFO, MedicLatina, LILACS, SciELO and Academic Search Complete. The search strategy did not consider a timeline as an eligibility criterion. The qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The analysis of the self-report questionnaire (PG-13), administered six months later, confirmed the absence of a diagnosis of complicated grief in the participants [33]. Furthermore, during the baseline phase of the study, quantitative data confirmed the presence of symptomatology related to post-traumatic stress disorder in 50% of the participants, while 20% suffered from relational dyadic stress, thus showing low levels of couple satisfaction and disturbances in the parental affective sphere [24].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The analysis of the self-report questionnaire (PG-13), administered six months later, confirmed the absence of a diagnosis of complicated grief in the participants [33]. Furthermore, during the baseline phase of the study, quantitative data confirmed the presence of symptomatology related to post-traumatic stress disorder in 50% of the participants, while 20% suffered from relational dyadic stress, thus showing low levels of couple satisfaction and disturbances in the parental affective sphere [24].…”
Section: Discussionmentioning
confidence: 68%
“…Typically, people rely on religion and spirituality to cope with periods of high emotional stress and declining health [32]. Moreover, the spiritual/religious dimension aids in finding meaning amid the most difficult and challenging circumstances [33], such as the traumatic experience of the COVID-19 pandemic [33,34]. In particular, those grieving may find comfort in viewing death as a passage and in maintaining a bond with the departed [35], often managing anger more effectively than those who feel abandoned by a higher power [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation